UPAYA PENINGKATAN PENGUASAAN VOCABULARY MENGGUNAKAN METODE TOTAL PHYSICAL RESPONSE DENGAN MEDIA CHARADE GAMES - Fransiska Gadis Marcella; Nyoto Harjono; Gamaliel Septian Airlanda (JURNAL TEMATIK, 2019)
This study aims to improve vocabulary mastery using the TPR method with charade games media. Type of this research is Classroom Action Research. There were 26 students in grade 3 of SD Negeri Pabelan 1 studied. The research instruments used were teacher observation sheets and residuals, as well as structured tests. The results showed that there was an increase in the activities of teachers and students from cycle I and cycle II by applying the TPR method with an average score of teacher activity not experiencing an increase or a decrease of 10 with a percentage of 100%, both in cycle I and cycle II. The average score of student activity has increased, in the first cycle the average score of student activity was 25.5 with a percentage of 63.75%, then in the second cycle the average score increased to 36 with a percentage of 90%. While the completeness of vocabulary mastery in the first cycle of students who reached KKM (minimum passing grade) amounted to 17 students or 65% then increased in the second cycle which reached KKM of 24 students or 93%. Thus, the TPR method with charade games media can improve student vocabulary